Relationship between Corporate Social Responsibility and Crash Risk of Stock Price - Seyyed Ali Hosseini (Ph.D) (Shahid Bahonar University of Kerman, 2017)
Corporate Social Responsibility (CSR) for accountability in business could be regarded as the fundamental issue for organizational behavior in a society, and as the determinant of the environment for business expansion and the net worth of resources, as well as business responsibility against stakeholders. This study aims to examine the relationship between CSR and the crash risk of stock price in future in the companies listed in the Tehran Stock Exchange (TSE). To measure the CSR, 24 items of the report of board of directors, and to measure the future stock price crash, the negative conditional skewness of firms’ monthly returns, and then, down-to-up volatility of the stock prices in a financial year, were determined. The tests of hypotheses were carried out in pooled and panel data models, using data from sample firms in the TSE in the period 2009 to 2013. The findings for the first hypothesis showed that there is not significant relationship between CSR and future stock price crash, regarding the conditional skewness measure. However, the findings for the second hypothesis indicated that there is significant negative relationship between CSR and future stock price crash, regarding down-to-up volatility measure of the stock price.